2012
DOI: 10.1167/iovs.12-9732
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria DNA Replication and DNA Methylation in the Metabolic Memory Associated with Continued Progression of Diabetic Retinopathy

Abstract: Continued hypermethylation of the CpG sites at the regulatory region of POLG affects its binding to the mtDNA, compromising the transcriptional activity. Modulation of DNA methylation using pharmaceutic or molecular means could help maintain mitochondria homeostasis, and prevent further progression of diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 25 publications
5
105
0
1
Order By: Relevance
“…Hyperglycaemic memory has mainly been studied in shortterm (cell culture) or long-term animal models, such as the studies by Kowluru [5]. Therefore, the aim of this study was to evaluate a novel model of intermediate-term hyperglycaemic memory using islet transplantation to enable the study of subsequent early structural alterations in the neurovascular unit of the retina in diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycaemic memory has mainly been studied in shortterm (cell culture) or long-term animal models, such as the studies by Kowluru [5]. Therefore, the aim of this study was to evaluate a novel model of intermediate-term hyperglycaemic memory using islet transplantation to enable the study of subsequent early structural alterations in the neurovascular unit of the retina in diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Because DNA-me can be inherited during cell division, persistence of DNA-me changes might reflect metabolic history. This hypothesis is supported by experimental models showing persistent DNA-me changes (global or at specific loci related to complications) in zebrafish with hyperglycemia (35), diabetic patient-derived fibroblasts (36), and retinas from diabetic rats under poor glucose control (37). However, the cause-effect relationship between epigenetics and human metabolic memory is not yet fully clear.…”
mentioning
confidence: 97%
“…In a casecontrolled study of 168 patients with type 2 DM, the global DNA methylation status was shown to be associated with DR. Additionally, the DNA methylation status exhibited a strong correlation with the progression of DR [71,72]. Apart from the increased activity of Dnmts in the retina and its capillary cells [73], histone-modifying machinery is also affected in diabetes.…”
Section: The Role Of Epigenetics In the Pathogenesis Of Diabetic Retimentioning
confidence: 99%
“…Due to the lack of supporting histones, and the close proximity to the superoxide-generating electron transport chain, mtDNA is prone to oxidative damage [111,112]. In diabetes, the activity of retinal Dnmts is increased, and the mtDNA replication enzyme, the polymerase γ-1 (POLG1) gene, is hypermethylated and its binding at the D-loop is impaired, resulting in decreased mtDNA biogenesis [73].…”
Section: The Role Of Epigenetics In the Pathogenesis Of Diabetic Retimentioning
confidence: 99%